Blueprint for a Smart Nation (LEARNing Landscapes, 2010)
Canada is in desperate need of a national strategy that harnesses education and innovation to address the intellectual health of the nation, just as the Canada Health Act was created to protect and enhance the physical well-being of Canadians. A Canada Learning and Innovation Act (the "Smart Nation Act") would help close the longstanding productivity gap that exists between Canada and its peers, and reverse the decline in research and development investments. The Act will recognize the importance of lifelong learning, the need to invest in knowledge and talented people, and the opportunities for collaboration that will bring about new innovations.
Keywords: canada; education; intellectual health; physical well-being; innovation; life-long learning; collaboration